(untitled) (Per Musi, 2000)
Historical survey of W. A. Mozart ́s aria Per questa bella mano KV 612 from its composition in 1791 through the rediscovery of its original in 1979 to its most recent edition in 1996 by Tobias Glöckler. Analysis of the double bass performance and notation practices in the classical period, focusing on the third-fourth tuning of the Vienese violone. It also presents new additions to the voice and double bass repertory: the first editions of Johannes Sperger ́s Selene, del tuo fuoco non mi parlarand Adolph Müller ́sLied an den Kontrabassand the translations of the original German and Italian lyrics of the three pieces into Portuguese.